Comparing national probability and community-based samples of sexual minority adults: Implications and recommendations for sampling and measurement - Krueger, Evan A. (Arch Sex Behav, 2020)
Scientific evidence regarding sexual minority populations has generally come from studies based on two types of samples: community-derived samples and probability samples. Probability samples are lauded as the gold standard of population research for their ability to represent the population of interest. However, while studies using community samples lack generalizability, they are often better able to assess population-specific concerns (e.g., minority stress) and are collected more rapidly, allowing them to be more responsive to changing population dynamics. Given these advantages, many sexual minority population studies rely on community samples. To identify how probability and community samples of sexual minorities are similar and different, we compared participant characteristics from two companion samples from the Generations Study, each designed with the same demographic profile of U.S. sexual minority adults in mind. The first sample was recruited for a national probability survey, whereas the second was recruited for a multi-community sample from four U.S. cities. We examined sociodemographic differences between the samples. Although there were several statistical differences between samples, the effect sizes were small for sociodemographic characteristics that defined the sample inclusion criteria: sex assigned at birth, race/ethnicity, and age cohort. The samples differed across other characteristics: bisexual respondents, respondents with less education, and those living in non-urban areas were underrepresented in the community sample. Our findings offer insights for recruiting community samples of sexual minority populations, and for measuring sexual identity on probability surveys. They also bolster confidence in well-designed community samples as sources for data on sexual minority populations.